Primary Ewing Sarcoma of the First Rib Presenting as Superior Vena Cava Syndrome: Case Report of a Young Male - Deepak Kumar Garnaik; B. Jagdish; Enono Yhoshu; Vivek Singh; Raja Lahiri; Satya Sree Balija (Journal of Indian Association of Pediatric Surgeons)
Ewing sarcoma is a malignant tumor of young adults comprising about 10%–15% of all bone sarcomas. Commonly, the long bones are affected but it can also originate from the rib, pelvis and spine. We present a large Ewing sarcoma in a 16-year-male, arising from the first right rib and manifesting with superior vena cava syndrome.